Predictors of preterm birth in patients with mild systemic lupus erythematosus. Issue 9 (29th January 2013) - Clowse, Megan E B; Wallace, Daniel J; Weisman, Michael; James, Andra; Criscione-Schreiber, Lisa G; Pisetsky, David S
Abstract : Objective: While increased disease activity is the best predictor of preterm birth in women with systemic lupus erythematosus (SLE), even women with low disease activity are at increased risk of this complication. Biomarkers that would identify at-risk pregnancies could allow interventions to prevent preterm birth. Method: Measures of SLE activity, inflammation, placental health and renal function between 20 and 28 weeks gestation (mid-gestation) were correlated to preterm birth and gestational age at delivery in a prospective cohort of pregnant women with SLE. Result: Of the 40 pregnancies in 39 women, all with mild–moderate SLE disease, 9 (23.7%) of the 38 live births were delivered preterm. Low C4 was the only marker of SLE activity associated with younger gestational age at delivery. Elevated ferritin and lower oestradiol correlated with younger gestational age at delivery. Renal function remained normal during all pregnancies at mid-gestation and did not correlate with preterm birth. Higher serum uric acid, however, correlated with younger gestational age at delivery. Conclusions: In women with SLE with mild–moderate disease activity, ferritin, oestradiol and uric acid levels at mid-gestation may predict preterm birth. These markers may prove to be clinically useful in identifying pregnancies at particularly high risk for adverse outcomes.